Recurrent self-healing painful ecchymoses and fever: a case of Gardner-diamond syndrome - M. G., Sachanidou; G. D., Arampatzis; A., Zioga; G., Gaitanis; Bassukas, Ioannis D. (International Journal of Advances in Medicine, 2017)
Gardner - Diamond syndrome (GDS) is a rare recurrent condition of painful ecchymoses without apparent eliciting factors. We report a 40-year old woman with GDS without psychiatric comorbidity. She presented with, recurrent episodes of spontaneous, self-limiting corps of painful ecchymotic bruising and fever. Her medical history, physical and psychiatric examinations, a focused imaging work up and bone marrow biopsy were unremarkable; the skin biopsy excluded vasculitis. However, the erythrocyte autosensitization test was positive; a finding that together with history and clinico-laboratory results highly suggests GDS.